Exploring genetic associations between immune cells and hypertensive disorder of pregnancy using Mendelian randomization - Jingting Liu; Yijun Dong; Yawei Zhou; Wendi Wang; Yan Li; Jianying Pei (BMC, 2024)
Abstract Background Observational epidemiological studies suggested that immunological dysregulation and inflammation play a significant role in the placental and renal dysfunction that leads to maternal hypertension. The immunophenotypes' possible causalities with hypertensive disease of pregnancy remain ambiguous. We performed two-sample Mendelian randomization (MR) analyses to comprehensively investigate the causal effect of immunophenotypes on hypertensive disorder of pregnancy (HDP). Methods The large-scale genome-wide association studies (GWASs) data on immunological traits was taken from public catalog for 731 immunophenotypes. The summarized GWAS data in 4 types of HDP were retrieved from FinnGen database, including 811,605 Finnish individuals. The primary analysis was the inverse variance weighted (IVW) method, supplemented by conducting sensitivity analysis. To confirm whether cardiovascular proteins mediated the causal effect of immune cells on HDP, we additionally executed a mediation MR study. Results After looking into genetically predicted immunophenotype biomarkers, we discovered 14 highly correlative immunophenotypes and 104 suggestive possible factors. The IVW analysis indicated that HLA DR on myeloid DC, HLA DR on plasmacytoid DC, and HLA DR on DC had a significant association with pre-eclampsia/eclampsia (PE), whereas CD4+ CD8dim AC and CD4+ CD8dim % leukocyte were protective against gestational hypertension (GH). All of HDP in our study had no statistically significant impact on immune cells, according to reverse MR analysis. The mediating role of LOX-1between HLA DR on plasmacytoid DC and chronic hypertension prior to pregnancy was validated. Conclusion This study showed that many immunophenotypes are implicated in HDP. Furthermore, the level of LOX-1 mediated the pathophysiology relationship between HLA DR on plasmacytoid dendritic cells and chronic hypertension prior to pregnancy.